2012
DOI: 10.4093/dmj.2012.36.6.422
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes and Impaired Glucose Regulation with Associated Cardiometabolic Risk Factors and Depression in an Urbanizing Rural Community in Bangladesh: A Population-Based Cross-Sectional Study

Abstract: BackgroundTo determine the prevalence of type 2 diabetes (T2DM) and impaired glucose regulation (impaired fasting glucose [IFG] and impaired glucose tolerance [IGT]) in an urbanizing rural population of Bangladesh and associated cardiometabolic risk indicators and depression.MethodsA total of 2,293 subjects aged ≥20 years in an urbanizing rural Bangladeshi community were investigated. Socio-demographic and anthropometric details, blood pressure, fasting plasma glucose (FPG), 2 hours after 75 g plasma glucose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…The recruitment methods and examination procedures of this rural study have been described before1820. A total of 10 villages were randomly selected from 25 villages in the region.…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment methods and examination procedures of this rural study have been described before1820. A total of 10 villages were randomly selected from 25 villages in the region.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these herbal remedies are important objects of research, especially in context of the virtually exploding prevalence of diabetes mellitus in Bangladesh. Although diabetes is more prevalent in urban areas [16,17], in rural communities prevalence rates for diabetes rose from 2.3% to 6.8% in between 1999 to 2004 [18]. …”
Section: Introductionmentioning
confidence: 99%
“…3 In another study, Nosratzehi et al (2015) showed the mean fasting blood glucose in patient with oral lichen planus was 95. 6 found the prevalence of diabetes mellitus 7.9% and impaired glucose tolerance 4.0% in Bangladesh community. Current study showed high prevalence of diabetes mellitus and impaired glucose tolerance 37.5 and 18% respectively in patients with lichen planus.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of impaired glucose tolerance is 4.0% in Bangladeshi population. 6 Diabetes and impaired glucose tolerance can be diagnosed by using American Diabetes Association (ADA) criteria. Insulin resistance also indicates relatively high-risk for future development of diabetes.…”
mentioning
confidence: 99%